Feasibility study assessing equitable delivery of newborn pulse oximetry screening in New Zealand's midwifery-led maternity setting. Issue 8 (17th August 2019) - Cloete, Elza; Gentles, Thomas L; Dixon, Lesley A; Webster, Dianne R; Agnew, Joshua D; Davidkova, Sarka; Alsweiler, Jane M; Rogers, Jenny; Bloomfield, Frank H
Abstract : Objectives: The aim of this study was to conduct New Zealand-specific research to inform the design of a pulse oximetry screening strategy that ensures equity of access for the New Zealand maternity population. Equity is an important consideration as the test has the potential to benefit some populations and socioeconomic groups more than others. Setting: New Zealand has an ethnically diverse population and a midwifery-led maternity service. One quaternary hospital and urban primary birthing unit (Region A), two regional hospitals (Region B) and three regional primary birthing units (Region C) from three Health Boards in New Zealand's North Island participated in a feasibility study of pulse oximetry screening. Home births in these regions were also included. Participants: There were 27 172 infants that satisfied the inclusion criteria; 16 644 (61%) were screened. The following data were collected for all well newborn infants with a gestation age ≥35 weeks: date of birth, ethnicity, type of maternity care provider, deprivation index and screening status (yes/no). The study was conducted over a 2-year period from May 2016 to April 2018. Results: Screening rates improved over time. Infants born in Region B (adjusted OR=0.75; 95% CI 0.67 to 0.83) and C (adjusted OR=0.29; 95% CI 0.27 to 0.32) were less likely to receive screening compared with those born in Region A. There were significant associations between screening rates and deprivation, ethnicity and maternity care provider. Lack of human and material resources prohibited universal access to screening. Conclusion: A pulse oximetry screening programme that is sector-led is likely to perpetuate inequity. Screening programmes need to be designed so that resources are distributed in the way most likely to optimise health outcomes for infants born with cardiac anomalies. Ethics approval: This study was approved by the Health and Disability Ethics Committees of New Zealand (15/NTA/168).